Melioidosis: A Rare Cause of Liver Abscess - Peter Franz M. San Martin; Catherine S. C. Teh; Ma. Amornetta J. Casupang (Case Reports in Hepatology)
Case Presentation. This is a case of a 44-year-old male, farmer, known to be diabetic, presenting with two-week history of vague abdominal pain associated with high grade fever. Abdominal CT scan showed localized liver abscess at segment 8 measuring 7.5 × 6.8 × 6.1 cm. Patient subsequently underwent laparoscopic ultrasound guided pigtail insertion for drainage of abscess. Culture studies showed moderate growth of Burkholderia pseudomallei in which the patient completed seven days of IV Meropenem. On follow-up after 12 weeks of oral Sulfamethoxazole/Trimethoprim, taken twice a day, the patient remained asymptomatic with no residual findings based on the abdominal ultrasound. Discussion. Diagnosis of melioidosis, a known “great masquerader,” relies heavily on culture studies. Consensus with regard to the management of liver abscess caused by Burkholderia pseudomallei has not yet been established due to the rarity of cases. Surgical intervention through either a percutaneous or open drainage has shown good outcomes compared to IV antibiotics alone. In Philippines, the possibility of underreporting is highly plausible. This write-up serves not only to report a rare presentation of melioidosis but also to add to the number of cases reported in the country, possibly indicative of disease emergence.